2019
DOI: 10.1039/c9dt00017h
|View full text |Cite
|
Sign up to set email alerts
|

Ag NPs decorated on a COF in the presence of DBU as an efficient catalytic system for the synthesis of tetramic acids via CO2 fixation into propargylic amines at atmospheric pressure

Abstract: Ag NPs are decorated at the surface of a COF material TpPa-1 and the resulting Ag@TpPa-1 catalyzes efficiently for the synthesis of tetramic acids from a variety of propargylic amines using CO2 as reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 68 publications
3
37
0
Order By: Relevance
“…The highest catalytic activity of Ag. NPs could be attributed in terms of their maximum surface area7.38m 2 /g with total pore volume as 0.0389 mL/g and average pore radius as 1.0964 nm 61 .
Figure 8 Nitrogen adsorption/desorption isotherms of Ag.
…”
Section: Resultsmentioning
confidence: 99%
“…The highest catalytic activity of Ag. NPs could be attributed in terms of their maximum surface area7.38m 2 /g with total pore volume as 0.0389 mL/g and average pore radius as 1.0964 nm 61 .
Figure 8 Nitrogen adsorption/desorption isotherms of Ag.
…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the conversion does not transpire in the absence of the COF confirms that the COF plays a key role in trapping and activating the CO 2 molecules. There are few reports on CO 2 conversion using COF where epoxides and propargyl amines are being used as the reagent for chemical fixation . But, to the best of our knowledge, this is the first report of COF based heterogeneous catalyst to convert CO 2 into α‐alkylidene cyclic carbonates using propargyl alcohols with high selectivity and yields.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the characteristic diffraction peaks of Ag NPs at 37.7, 44.0, and 64.1 correspondingly belonging to the (111), (202), and (220) facets were clearly observed in Ag@DhaTph-COOH. 77 The N 2 adsorption isotherm of Ag@DhaTph-COOH indicated that its N 2 adsorption capacity and BET surface area decreased to 224.6 cm 3 g À1 and 259.3 m 2 g À1 , respectively (Fig. 1c), which was undoubtedly caused by the partial pore occupation of Ag NPs.…”
Section: Resultsmentioning
confidence: 93%